The Role of Social Media Usage and Knowlegde in the Banking Sector in South Jakarta - Putra, Andreas Wahyu Gunawan; Hutama, Rizvaldy Ananta; Aseanty, Deasy (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the effect of Work-related Social Media Usage, Social- related Social Media Usage and Knowledge Sharing on Employee Engagement on banking employees in South Jakarta. The independent variables are Work-related Social Media Usage and Social-related Social Media Usage. The intervening variable is Knowledge Sharing and the dependent variable is Employee Engagement. The research was conducted using purposive sampling method by taking samples using google form to employees who work in banking companies in South Jakarta. From the sampling, 157 samples were collected. Data analysing using AMOS applications with the Structural Equation Modeling (SEM) method. The results showed there was an influence on Work-related Social Media Usage, Social-related Social Media Usage and Knowledge Sharing on Employee Engagement to support employee performance. There is no indirect effect of Work-related Social Media Usage and Social-related Social Media Usage on Employee Engagement through Knowledge Sharing. This research provides practical implications in increasing employee engagement using working using social media tools.